The rise and fall of nuclear phase-out in South Korea: German model and the dynamics of policy learning - Min, In Young (The Pacific review, 2025)
South Korea’s nuclear energy policy has experienced sharp reversals over the past decade, shifting from a planned nuclear phase-out to renewed promotion. This article examines the drivers of these shifts with particular attention to the role of Germany’s nuclear phase-out policy as both an inspiration and a foil. Drawing on scholarship on policy diffusion and social norms, I argue that while international policy models travel across borders, their interpretation and implementation are shaped by domestic political contestation and deeply rooted societal norms. In South Korea, Germany’s decision to abandon nuclear power provided a powerful precedent for the Moon administration’s phase-out policy, which gained traction amid rising safety concerns. Yet the enduring norm that nuclear energy is vital for economic development—reinforced by South Korea’s export orientation and ambitions to sell reactors abroad—undermined this policy. The Russian invasion of Ukraine and Europe’s subsequent energy crisis further shifted the policy discourse, turning Germany from role model to cautionary example. South Korea’s case illustrates how global policy lessons can be refracted through domestic norms to produce divergent outcomes, and how the same international reference point can serve both as exemplar and foil over time.